YIELD OF CERVICAL MEDIASTINOSCOPY IN DIAGNOSIS OF INDETERMINATE MEDIASTINAL lYMPHADENOPATHY/MASSES AND STAGING OF LUNG CANCER - Khan, Muhammad Imtiaz; Muzaffa, Muhamamd Sultan; Zulfiqar, Mujahid; Subhani, Shahzadi Samar (Pakistan Armed Forces Medical Journal, 2011)
Objective:To determine the yield of cervical mediastinoscopy in indeterminate antero-superior mediastinal lymphadenopathy or masses and in staging of non small cell carcinoma lung. Study Design: Descriptive prospective study Place and Duration of Study: Thoracic Surgical unit of Combined Military Hospital Rawalpindi from Jan 2007 to June 2009. Patients and Methods: Patients were placed in group I for diagnostically indeterminate antero superior mediastinal lymphadenopathy/masses and in group II for staging of non small cell lung cancer (NSCLC) with enlarged mediastinal lymph nodes on CT scan (greater than 10 mm on short axis). All patients underwent the procedure under general anaesthesia. A plane anterior to trachea was developed using blunt finger dissection until carina. Biopsies of the mass or lymph nodes were taken and sent for histopathology. In case of staging for Carcinoma lung, lymph node stations 2L, 2R, 4L, 4R and 7 were searched and biopsied and sent in appropriately labelled containers for histopathology. Patients were usually discharged on the same day. Results: Forty eight cases were included in this study during the course of 2 ½ years of period. Twenty nine cases were included in group I and nineteen in group II. In group I chronic caseating granulomas due to tuberculosis were the most cause in 45 % of cases followed by 24% cases of lymphoma. In group II, 4 (21%) cases revealed no evidence of malignancy in any lymph nodes and in 11 (57.9%) cases only ipsilateral mediastinal lymph nodes were involved by tumor making it N2 disease. In 4 (21%) cases contra lateral mediastinal lymph nodes were involved by tumor making it N3 disease. Mortality in this study was only one case (3.4%). Conclusion: Mediastinoscopy is minimally invasive, cost effective and simple procedure in trained hands for both diagnosis and staging purpose.